Organisational complexity of the Eurofighter Typhoon collaborative supply chain - Matthews, Ron; Al-Saadi, Rashid (Taylor & Francis, 2023)
The European Union (EU) promotes arms collaboration as a stepping-stone towards the evolution of an integrated European defence technology and industrial base. It will necessarily comprise prime contractors and their attendant supply chains, with the latter particularly important because they represent a refined regional division of labour, promoting efficiencies through skill-based specialisation. Paradoxically, however, Europe’s largest military aerospace collaborative venture, the Eurofighter Typhoon, possesses a complex supply chain subject to political and institutional strictures, as well as potential inefficiencies. Partner nations prioritise national sovereignty objectives through duplicated assembly lines and work allocation arrangements based on juste retour (fair share) rather than market-driven competitiveness criteria. The purpose of this paper, then, is to explore Typhoon’s supply chain complexity, especially the impact of juste retour policy. The findings from this analysis will highlight important policy issues influencing the future supply chain model of Europe’s successor 6th-Generation fighter programme.
Keywords: Eurofighter typhoon; arms collaboration; defence supply chains; tempest fighter; juste retour